(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
This article is about an honorary citizen of France,an English Voltaire,an American revolutionary,the author of the revolutionary book ‘Common Sense’, a defender of human rights,one of the fathers of American Independence,a person who actively fought against slavery.